Effect of Destillation Temperature on Quality and Yield of Patchouli Oil of Direct Steam Destillation Type - Hamjah Dalimunthe; Lukman Adlin Harahap; Achwil Putra Munir (Jurnal Rekayasa Pangan dan Pertanian, 2015)
On direct steam destilation type, destillation temperature needs to be considered. The temperature determines the quality of destilation product. This study tested various temperature on destillation of volatile oil in direct steam type destilation. The study was conducted at the Laboratory of Agricultural Engineering and analysis was done in Food Chemical Analysis Laboratorium Faculty of Agricultural in September 2014 to October 2014 A non-factorial completely randomized design with 95°C, 100°C and 105°C was used. Parameters measured were water content, free fatty acid and yield. The results showed that the temperature had  significant effect on yield. The best treatment was the U3 treatment (105°C) which produced 21,1% water content, and 0,44% yield. Key word: Destillation temperature, direct steam, patchouli oil